Fillers as Communication Strategies Uttered by Prabowo Subianto in His Interview as President-Elect at the Qatar Economic Forum - Endang Susilowati; Etika Dewi Kusumaningtyas (Universitas An Nuur, 2024)
In the realm of political communication, the ability to convey messages effectively in international forums is crucial for leaders to shape their public image and perception. Fillers, often dismissed as marks of speech disfluency, can serve strategic functions in managing communication flow and engaging listeners. Some studies investigated the use of fillers in spoken communication, but none has focused on Indonesian political leaders. This article reports on a study that aims to examine the types and functions of fillers as communication strategies uttered by Prabowo Subianto in his interview as president-elect at the Qatar Economic Forum. This is a qualitative study that employs a conversation analysis. The data were collected from the interview video derived from YouTube which were then transcribed. The transcription was analyzed by using Rose’s (1998) theory of types of fillers and Stenstrom’s (1994) taxonomy of functions of fillers. This study reveals two major findings. First, in terms of the types of fillers, the results show that Prabowo uttered both unlexicalized and lexicalized filled pauses, dominated by lexicalized fillers. However, the unlexicalized filler “uh” was uttered most frequently. These results indicate that Prabowo tended to use both lexeme and non-lexeme words to fill the pauses. In terms of the functions of fillers, the findings show that Prabowo strategically used fillers as hesitating, time-creating, empathizing, mitigating, and editing term. He produced fillers most frequently for hesitating, which signifies that he uttered fillers to hesitate and gain more time to think of what to say next. This study contributes to a deeper understanding of how political leaders utilize fillers to enhance communication effectiveness, especially in high-stakes international settings. Finally, this study provides some pedagogical implications for teaching speaking to learners of English as a foreign language.